PENDAMPINGAN SERTIFIKASI HALAL BERBASIS SELF-DECLARE BAGI UMKM DI SUKODADI - Moch. Zainul Arifin; Elva Imeldatur Rohmah; Moh. Faizur Rohmah; Imatus Solichah (As-Sidanah, 2025)
Halal certification plays an important role for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, especially in Sukodadi District, Lamongan Regency. However, the low understanding and awareness of business actors regarding the benefits and procedures of halal certification is a major obstacle. Many MSMEs consider this process to be complicated, costly and does not provide significant economic benefits. Therefore, this community service activity aims to increase understanding and assist MSMEs in obtaining halal certification through a self-declare scheme. The method used in this activity is Participatory Action Research (PAR), which involves the active participation of MSMEs in each stage, namely planning, implementation, and evaluation. Assistance was provided to ten MSMEs with various types of products, including socialization, facilitation of the creation of Business Identification Numbers (NIB), and submission of halal certification through the SIHalal system. As a solution to the limited quota of free halal certification from the government, facilitators registered MSMEs through a simpler and faster self-declare scheme. The results of this assistance show that all assisted MSMEs have successfully obtained halal certification from BPJPH, with nine of them also being assisted in the NIB creation process. In addition, this activity increases the understanding of business actors regarding the urgency of halal certification. It opens up opportunities for wider market access, including to supermarket chains and modern stores. This program also strengthens social networks between MSMEs and increases local community awareness of the importance of halal-certified products.